Perbankan Syariah; Restrukturisasi Utang; Kepatuhan Syariah; Fikih Muamalah - Syhabudin, Abu; Dedi, Dedi; Kurnia Rusmiyati; Jaelani, Alan (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to evaluate the effectiveness of debt restructuring in syariah banking by exploring three key perspectives i.e., institutional policy, customer perception, and Islamic legal scholarship. Using BJB Syariah Majalengka as a case study, the research investigates how the bank’s restructuring mechanisms align with Fatwa DSN-MUI No. 48/DSN-MUI/II/2005 and principles of Fiqh Muamalah. The study employs a qualitative approach, combining document analysis, in-depth interviews with bank officials and fiqh scholars, and structured questionnaires distributed to customers who have undergone restructuring. The findings reveal that BJB Syariah has implemented debt restructuring through rescheduling, restructuring, and reconditioning while maintaining the syariah-compliant framework. From the customers’ perspective, debt restructuring is perceived as a supportive solution during financial hardship, yet knowledge gaps about their rights and obligations persist. Meanwhile, fiqh scholars emphasize that the legitimacy of restructuring hinges on justice, transparency, and the avoidance of prohibited elements such as riba, gharar, and unjust enrichment (dzulm). This triangular perspective highlights the need for stronger integration between policy, customer literacy, and shariah oversight.